Career Barriers of Chinese Self-Expatriate Women: Neither Double Jeopardy nor Ethnic Prominence - Bozionelos, Nikos (Frontiers in Psychology, 2020)
The study explored barriers to career progression of Chinese self-initiated expatriate (SIE) women in the United Kingdom using semi-structured interviews with two matched samples of Chinese SIE and native Caucasian British women. Double jeopardy and ethnic prominence offered the theoretical backdrop. Common gender-related career hindering factors emerged in both groups. However, no barriers due to ethnicity per se emerged for the Chinese SIE women, whilst their narrations revealed that the Chinese stereotype had rather facilitated their careers in the host country. Furthermore, they did not view self-expatriation as a particularly challenging endeavour. None of the two interpretative frameworks deployed, double jeopardy and ethnic prominence, could account for the findings. The study implies that the effects of ethnicity on self-expatriation experiences and outcomes may be contingent on SIEs’ ethnic and cultural origins. In addition, the findings imply that women who self-expatriate to escape gendered opportunities in their home countries may face similar gender-related barriers in host countries.